Randomized trial of inosine for urate elevation in amyotrophic lateral sclerosis. Issue 5 (14th March 2023) - Walk, David; Nicholson, Katharine; Locatelli, Eduardo; Chan, James; Macklin, Eric A.; Ferment, Valerie; Manousakis, Georgios; Chase, Marianne; Connolly, Mariah; Dagostino, Derek; Hall, Meghan; Ostrow, Joseph; et al.
Abstract: Introduction/Aims: Higher urate levels are associated with improved ALS survival in retrospective studies, however whether raising urate levels confers a survival advantage is unknown. In the Safety of Urate Elevation in Amyotrophic Lateral Sclerosis (SURE‐ALS) trial, inosine raised serum urate and was safe and well‐tolerated. The SURE‐ALS2 trial was designed to assess longer term safety. Functional outcomes and a smartphone application were also explored. Methods: Participants were randomized 2:1 to inosine (n = 14) or placebo (n = 9) for 20 weeks, titrated to serum urate of 7–8 mg/dL. Primary outcomes were safety and tolerability. Functional outcomes were measured with the Amyotrophic Lateral Sclerosis Functional Rating Scale Revised (ALSFRS‐R). Mobility and ALSFRS‐R were also assessed by a smartphone application. Results: During inosine treatment, mean urate ranged 5.68–6.82 mg/dL. Treatment‐emergent adverse event (TEAE) incidence was similar between groups ( p  > .10). Renal TEAEs occurred in three (21%) and hypertension in one (7%) of participants randomized to inosine. Inosine was tolerated in 71% of participants versus placebo 67%. Two participants (14%) in the inosine group experienced TEAEs deemed related to treatment (nephrolithiasis); one was a severe adverse event. Mean ALSFRS‐R decline did not differ between groups ( p  = .69). Change in measured home time was similar between groups. Digital and in‐clinic ALSFRS‐R correlated well. Discussion: Inosine met pre‐specified criteria for safety and tolerability. A functional benefit was not demonstrated in this trial designed for safety and tolerability. Findings suggested potential utility for a smartphone application in ALS clinical and research settings.